Augmenting stability and performance in perovskite solar cells: A critical review on perovskite-polymer synergy - Gayathry, Ganesh; Amina, Yasin; Izan Izwan, Misnon; Azhar, Fakharuddin; Schmidt-Mende, Lukas; Mohd Hasbi, Ab. Rahim; Jose, Rajan; Thomas, Sabu (Elsevier Ltd, 2023)
Perovskite solar cells (PSCs) are intensively studied over the past decade to enhance the renewable contribution to the total energy mix; however, their market potential is hampered mostly by their poor operational stability. Polymers as encapsulants, UV-filters, charge transport layers, and interfacial layers are shown to be a potential remedy not only to improve stability but also to positively contribute to other figures of merits of solar cells. Highly efficient PSCs (>15 %) with prolonged operational stability (>3000 h) in various device architectures including fibres, yarns, and woven and knitted cloths are reported using perovskite embedded polymers. This article critically and comprehensively reviews the synergistic interactions between various polymers and the organic–inorganic lead halide perovskite material to establish a structure–property correlation and to examine the viability of the PSCs technology for practical deployment. Mechanistic details of polymers in the photoactive, charge transport and interfacial layers on the morphology, optical and photovoltaic properties, and stability are analysed and discussed. Particularly on stability, the role of polymers on defect tolerance, phase and structure evolution, and external stimuli (heat, moisture, light, electric field, and oxygen) are elaborated. The dielectric properties of polymers enable them to be superior encapsulants over their corresponding monomers or other organic molecules. Based on these broad considerations, adopting the polymeric approach is shown to be a more efficient and greener leap towards the sustainable commercialization of perovskites.